Acquisition and processing of marine seismic data - Dondurur, Derman (Elsevier, 2018)
Acquisition and Processing of Marine Seismic Data demonstrates the main principles, equipment required and suitable selection parameters in 2D/3D marine seismic data acquisition. It also examines theoretical principles of 2D marine seismic data processing and their practical implications. Featuring detailed datasets and examples, the book helps relate theoretical background to real seismic data and contains important QC analysis methods and results, both for data acquisition and marine seismic data processing. Originally published by the Turkish Chamber of Engineers and Architects, the book is a valuable tool for researchers and students in geophysics, marine seismics, seismic data, and oil and gas exploration